2017
DOI: 10.1016/j.bbi.2016.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal alcohol exposure potentiates chronic neuropathic pain, spinal glial and immune cell activation and alters sciatic nerve and DRG cytokine levels

Abstract: A growing body of evidence indicates that prenatal alcohol exposure (PAE) may predispose individuals to secondary medical disabilities later in life. Animal models of PAE reveal neuroimmune sequelae such as elevated brain astrocyte and microglial activation with corresponding region-specific changes in immune signaling molecules such as cytokines and chemokines. The aim of this study was to evaluate the effects of moderate PAE on the development and maintenance of allodynia induced by chronic constriction inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
77
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(90 citation statements)
references
References 113 publications
11
77
2
Order By: Relevance
“…The role of LFA-1 in pathological pain was first explored in work by Noor et al that revealed prenatal alcohol exposure (PAE) predisposes adult rats to develop neuropathic pain in response to a minor injury. They found that LFA-1 expression is increased on microglia and trafficking immune cells in the lumbar spinal cords and on peripheral immune cells of neuropathic PAE rats (192). It was later identified that intrathecal or intravenous administration of BIRT-377, a small molecule non-competitive LFA-1 antagonist, relieves allodynia in neuropathic rats, which was associated with decreased immunoreactivity for spinal markers of glial activation and IL-1β and concurrent increases in IL-10 immunoreactivity (193,194).…”
Section: Lymphocyte Function-associated Antigen-1mentioning
confidence: 99%
“…The role of LFA-1 in pathological pain was first explored in work by Noor et al that revealed prenatal alcohol exposure (PAE) predisposes adult rats to develop neuropathic pain in response to a minor injury. They found that LFA-1 expression is increased on microglia and trafficking immune cells in the lumbar spinal cords and on peripheral immune cells of neuropathic PAE rats (192). It was later identified that intrathecal or intravenous administration of BIRT-377, a small molecule non-competitive LFA-1 antagonist, relieves allodynia in neuropathic rats, which was associated with decreased immunoreactivity for spinal markers of glial activation and IL-1β and concurrent increases in IL-10 immunoreactivity (193,194).…”
Section: Lymphocyte Function-associated Antigen-1mentioning
confidence: 99%
“…The total number of positive and negative responses were then entered into the computer software program, PsychoFit (http://psych.colorado.edu/~lharvey: RRID: SCR_015381) to determine the absolute withdrawal threshold (50% paw withdrawal threshold), as previously described [50] . The PsychoFit program fits a Gaussian integral psychometric function to the observed withdrawal rates for each monofilament using a maximum-likelihood fitting method [47,51] . The interpolated 50% withdrawal thresholds were then used for statistical analysis.…”
Section: Behavioral Assessment Of Hindpaw Mechanical Allodyniamentioning
confidence: 99%
“…Tissue collection was conducted in six cohorts of mice (8 mice in each cohort, N of 1 from each experimental condition) as previously described [47,51] and modified as described here. Immediately following behavioral analysis on Day 13 post-surgery (Day 3 post-injection), mice were deeply anesthetized under isoflurane (10 min in 5% isoflurane and in oxygen at 2 L/min), followed by rapid transcardial perfusion with ice cold 0.1 M phosphate buffered saline (PBS; pH = 7.4; flow rate 10 mL/min).…”
Section: Tissue Collection For Rna and Protein Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The centrally acting drugs (opiate analgesics) such as narcotics inhibited both phases equally, while antiinflammatory drugs (non-opiate analgesics) specially inhibited the second phase 20,21 . As we mentioned before it is also well known that the formalin model may involve sensorial C-fibers 22 in early phase and a combined process generated by peripheral inflammatory tissue and functional changes in the dorsal horn in late phase 23,24 .…”
Section: Formalin Testmentioning
confidence: 83%